THE INFLUENCE OF KNOWLEDGE ABOUT BREASTFEEDING MANAGEMENT IN REDUCING THE LEVEL OF ANXIETY IN WOMEN WITH POST CAESAREAN DELIVERY - Dewi Marfuah; Annisa Nurfitriani Bachri (Journal of Maternity Care and Reproductive Health, 2018)
Lactation management is management needed to support the success of breastfeeding. Based on the data obtained from Riskesdas in 2012, the incidence of early initiation of breastfeeding process in Indonesia was only 29.3%, one of the influencing factor was the condition of post-cesarean women. Breastfeeding process for women with cesarean would be very hard and cause psychological problems, such as anxiety. This study aimed to determine the relations between knowledge of lactation management and anxiety in the breastfeeding process in women post cesarean delivery. This study was a correlation study with cross-sectional approach. The number of samples was calculated using Slovin formula, 59 women involved in this study that chosen using purposive sampling technique. The data were collected using the Hamilton Rating Scale for Anxiety (HARS) questionnaires and lactation management knowledge questionnaires. The relations analysis was performed using Spearman Rank Correlation. The result showed that 54.2% of mothers have moderate knowledge and 39.0% of them experience mild anxiety. Therefore, there was a significant relationship between the breastfeeding process and anxiety ρ 0.001 <0.05. It can be concluded that there is a relation between knowledge of lactation management and anxiety in the breastfeeding process. Conclusion,  It is suggested that nurses should provide nursing care on postnatal period, especially on how to give the appropriate breastfeeding so that anxiety in the breastfeeding process in the post of cesarean can be prevented.Keywords: anxiety, breastfeeding, knowledge, lactation management, sectio caesarea